2021
DOI: 10.1186/s13031-021-00388-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for hypertension and diabetes among those screened in a refugee settlement in Uganda

Abstract: Background Diabetes and hypertension are increasingly prevalent in low and middle income countries, but they are not well documented in refugee settlements in these settings. We sought to estimate the prevalence and associated characteristics of diabetes and hypertension among adults presenting for clinic-based HIV testing in Nakivale Refugee Settlement in Uganda. Methods HIV-negative adults presenting to outpatient clinics for HIV testing at three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The study further unveiled those men are at a higher risk of having undiagnosed hypertension compared to women, corroborating findings from a study conducted in a refugee camp in Uganda 12 and results from a national survey in Kenya on the prevalence, awareness, treatment, and control, as well as determinants of hypertension Prevalence, awareness, treatment and control of hypertension and their determinants: results from a national survey 13 . These studies demonstrated that men were less likely to be aware of their hypertension status.…”
Section: Discussionsupporting
confidence: 77%
“…The study further unveiled those men are at a higher risk of having undiagnosed hypertension compared to women, corroborating findings from a study conducted in a refugee camp in Uganda 12 and results from a national survey in Kenya on the prevalence, awareness, treatment, and control, as well as determinants of hypertension Prevalence, awareness, treatment and control of hypertension and their determinants: results from a national survey 13 . These studies demonstrated that men were less likely to be aware of their hypertension status.…”
Section: Discussionsupporting
confidence: 77%
“…Our study is in line with the previous studies on yield and NNS for screening DM and hypertension in PTB patients and their families [11][12][13][14]. The values of NNS and yield were not directly comparable due to the difference in definitions of the two terms.…”
Section: Plos Onesupporting
confidence: 82%
“…Thus, hypertension screening should always accompany DM screening, and chronic conditions should be investigated as routine screening programs. This approach is particularly justified in some countries with obtaining the high yield of newly detected cases [11][12][13].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Burmese refugees in Australia have some level of awareness about the negative effects of smoking tobacco and chewing betel quid but little knowledge about the cessation of these habits [11]. Hypertension is widely prevalent among refugees and asylum seekers in Uganda, with a significant number of people unaware of their condition and consequently suffering from uncontrolled hypertension [12].…”
Section: Introductionmentioning
confidence: 99%